Ügyfél jogállás, bizonyításos mérlegelés és a megállapított jogkövetkezmények funkcióinak egyes kérdései a fogyasztóvédelmi hatóság eljárásában - Joó, Imre (Debreceni Jogi Műhely, 2015)
This study focuses on the issues related to the procedures of the Hungarian Authority for Consumer Protection. The article includes the main questions from the field of administrative law, such as the problems of the legal status of consumers and the use of sanctions. I used contextual and teleological methods of interpretation to demonstrate the problems and the possible solutions.